Obtaining the ideal smoked bacon: What is the influence of the product space and multivariate procedure to construct the external preference mapping? - Saldana, E (2019)
The authors are grateful to the São Paulo Research Foundation (FAPESP, Brazil), for funding the project No.2016/15012-2.Erick Saldaña would like to thank the ‘‘Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica"(CONCYTEC, Peru) for the Ph.D Scholarship (Contract 104-2016-FONDECYT).Mariana Marinho Martins and Beatriz Schmidt Menegali acknowledges Coordination for the Impro-vement of Higher Education Personnel (CAPES) for the MS cscholarship